Ethnic Conflict in World Politics: By Ted Robert Gurr and Barbara Harff. Dilemmas in World Politics Series. Boulder, CO: Westview Press, 1994, pp. 206. (American Journal of Islam and Society, 1997)
Thi publication comes at a time when unprecedented bloody ethnic conflictnot only dominate the global media and international politics, but also numb theworld's conscience. Bosnia Herzegovina, Somalia, Rwanda, Burundi, EastTimor, Chechnia, Kashmir, and Kurdistan are some of the famous landmarkswhere entire countries and communities are caught up in the web of ethnic conflict.In other instances, ethnic conflict is gradually becoming a feature ofnational life. It is not at all unfamiliar to hear reports of ethnic conflict in India(Hindu-Muslim riots), Germany (violence against immigrant Turks), France(anti-Arab right-wing nationalist fervor and the Muslim scarf issue), the UnitedStates (Los Angeles riots after the Rodney King trial) and Great Britain (Muslimand government standoff over Salman Rushdie's Satanic Verses).Gurr and Harff have written a useful book that tries to make sense of the causesof ethnic conflict in different parts of the world. It deals with the issue in thecontext of rapid changes in the world order; the emergence of ethnopoliticalgroups or ethnoclasses; the struggles for either autonomy or pluralism by variousethnic and social groups; the challenges that ethnopolitics poses to the international.legal and political systems; and the effect of this on communitiesdemanding ethnic rights. It also attempts to provide a framework for analysis ...